Game over too soon: early specialization and short careers in esports - Kang, Jimoon; Kim, Seongcheol (Frontiers in Psychology, 2025)
IntroductionEsports has become a global phenomenon, offering considerable professional opportunities, enhanced cognitive abilities, and strong social capital for young competitors. However, these benefits are often counterbalanced by significant challenges, including burnout, exploitation, and inconsistent governance, particularly for its predominantly young talent.MethodsIn this convergent mixed-methods study, we examine the factors influencing career longevity in esports by integrating a longitudinal analysis of 15,021 players’ records (1998–2023) and in-depth qualitative interviews conducted with ten key stakeholders in the Korean esports ecosystem.ResultsOur quantitative findings reveal an exponential increase in tournaments, prize money, and active competitors yet also expose a concerning trend: newer birth cohorts, especially those born after 1998, exhibit markedly shortened careers—with median durations approaching just 2 years. Complementary qualitative insights elucidate how early specialization, exploitative contractual practices, intense training regimens, and fragmented governance contribute to burnout and rapid career turnover.DiscussionTogether, these results underscore the urgent need for comprehensive policy reforms, including standardized contractual frameworks, holistic athlete support systems, and centralized regulatory oversight, to safeguard young talent and ensure the long-term sustainability of esports.